Outbreaks of African horse sickness in Senegal, and methods of control of the 2007 epidemic. (9th February 2013) - Diouf, N. D.; Etter, E.; Lo, M. M.; Lo, M.; Akakpo, A. J.
Abstract : Since first being detected in Nigeria in January 2007, African horse sickness virus serotype 2 (AHSV‐2) has spread throughout the northern hemisphere, and was first reported in Senegal. A retrospective study was conducted from December 2009 to April 2010 using data collected in the field combined with information available at the Direction of Veterinary Services. The epidemic started in the Dakar region with two outbreaks in March and June 2007, respectively, and spread in several parts of the country between July and November 2007. During this period, 232 outbreaks and 1137 horse deaths were reported. The epidemic was controlled by mass vaccination using a polyvalent‐attenuated vaccine. This retrospective study was conducted with various assumptions of AHSV‐2 introduction, and provides recommendations for implementing an early warning surveillance system for African horse sickness in Senegal.